Nutrição potássica como estratégia mitigadora do estresse salino no cultivo de meloeiro em ambiente protegido - Oliveira, Giordanio Bruno Silva (Universidade Federal Rural do Semi-Árido, 2020)
The use of saline water is one of the main challenges in agricultural production, as it can cause nutritional imbalance and, consequently, reduce crop yields. Thus, this work aimed to evaluate the efficiency of potassium nutrition as an attenuating agent of salt stress in melon cultivated in a protected environment. The experimental design used was in randomized blocks, in a 2 x 4 factorial scheme, with three replications, using a substrate based on coconut fiber and washed sand (2:1). The treatments have formed by the combination of two melon hybrids (Gália and Cantaloupe) with four nutrient solutions (S1- standard nutrient solution (2.5 dS m-1); S2 - salinizated nutrient solution with NaCl (5.0 dS m-1); S3 - salinizated nutrient solution with + 50% K (6.5 dS m-1); S4 - salinizated nutrient solution with NaCl + 100% K (7.5 dS m-1)). Plants have evaluated at 70 days after planting for the following variables. Physiological (chlorophyll a fluorescence, initial fluorescence, maximum fluorescence, maximum quantum efficiency of photosystem II, initial fluorescence before the saturation pulse, electron transport rate, CO2 assimilation rate, stomatal conductance, internal CO2 concentration, instant efficiency water use). Growth (length of the main branch, stem diameter, number of leaves, leaf area, specific leaf area, leaf area ratio, leaf succulence, dry mass of leaves, branches, fruits and total). Yield and post-harvest (fruit weight, fruit diameter, internal cavity, skin thickness, pulp thickness, pulp firmness, soluble solids, titratable acidity, soluble solids / titratable acidity ratio, pH, total sugars and vitamin C). Mineral nutrition (macronutrients and sodium). The data obtained have subjected to analysis of variance, and, the unfolding of the factors carried out when there was a significant response to the interaction between the factors. The effect of the treatments has analyzed using the means comparison test. Salinity and potassium concentrations had no effect on most chlorophyll fluorescence and gas exchange variables. Variable fluorescence, photochemical extinction coefficient, electron transport rate, stomatal conductance, transpiration and CO2 assimilation rate varied between cultivars. In growth, the application of saline nutrient solutions with extra concentrations of potassium reduced the length of the main branch, leaf area, dry mass of branches and total dry mass of melon plants. The McLaren cultivar reduced the dry mass of fruits in the solutions with the highest potassium concentration. In quality, the cultivar SV1044MF and McLaren showed, respectively, greater firmness of pulp and total sugars in the extra concentration of 100% potassium. The extra potassium fertilization in saline nutrient solutions did not result in benefits on the physiology and growth of melon plants. Saline solutions with extra potassium concentration negatively affected the fruit yield. The extra potassium concentration in saline nutrient solutions decreases the sodium content but had no effect on the levels of nitrogen, phosphorus, potassium, calcium and magnesium in melon cultivars
Keywords: Cucumis melo L.; Potássio; Salinidade; Melão nobre; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO